2015
DOI: 10.1093/molbev/msv110
|View full text |Cite
|
Sign up to set email alerts
|

Evolution ofCONSTANSRegulation and Function after Gene Duplication Produced a Photoperiodic Flowering Switch in the Brassicaceae

Abstract: Environmental control of flowering allows plant reproduction to occur under optimal conditions and facilitates adaptation to different locations. At high latitude, flowering of many plants is controlled by seasonal changes in day length. The photoperiodic flowering pathway confers this response in the Brassicaceae, which colonized temperate latitudes after divergence from the Cleomaceae, their subtropical sister family. The CONSTANS (CO) transcription factor of Arabidopsis thaliana, a member of the Brassicacea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 122 publications
(219 reference statements)
1
47
0
Order By: Relevance
“…Simon et al, proposed that a CO function has evolved in the Brassicaceae family only after the most recent genome duplication that occurred within the family and that is not shared by its sister family [33]. Evolution of such function created a flexible switch to trigger flowering under LD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simon et al, proposed that a CO function has evolved in the Brassicaceae family only after the most recent genome duplication that occurred within the family and that is not shared by its sister family [33]. Evolution of such function created a flexible switch to trigger flowering under LD.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons between rice and Arabidopsis can help to derive and test hypotheses concerning protein function, albeit these two species diverged ~150M years ago and the extent of conservation of the Hd1 - Hd3a / CO - FT modules is debated [32,33]. In Arabidopsis, CO can interact with several AtNF-YB and AtNF-YC subunits [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Heteromorphism in this lineage has been reported for six species (Solms-Laubach, 1901;Hedge, 1965), including Aethionema arabicum, a small diploid, annual, herbaceous plant whose genome sequence was published recently (Haudry et al, 2013). Analysis of the genome has shown that the genus Aethionema shares the ancient whole-genome duplication "At-alpha" with the crown-group Brassicaceae (Schranz et al, 2012); thus, it has been used for comparative molecular evolutionary analyses for several gene families (Hofberger et al, 2015;Mohammadin et al, 2015;Simon et al, 2015). The species has been described as forming two distinct fruit and seed morphs that may influence their propagation strategy (Solms-Laubach, 1901).…”
mentioning
confidence: 99%
“…CO -like sequences seem to exist in all plants. Recent evidence indicates that CO of Arabidopsis arose from a family-specific duplication and similar events might have occurred independently in many plant families (Simon et al, 2015). In contrast, plants from the Amaranthaceae family are lacking a true CO ortholog (Dally et al, 2014).…”
mentioning
confidence: 99%